Efektivitas Pembelajaran STEM dengan Model PjBL Terhadap Kreativitas dan Pemahaman Konsep IPA Siswa Sekolah Dasar - Indah Yulaikah; Sri Rahayu; Parlan Parlan (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2022)
Abstract: This study aims to examine the effectiveness of STEM learning with the PjBL model on creativity and conceptual understanding of elementary school students. The Research design used in this study is a quasi experimental design. The research subjects were 60 elementary school students who were divided into 2 homogeneous classes, consisting 30 students in the experimental class and 30 students in the experimental class.  Students in the control class were taught by conventional methods and in the experimental class were taught by STEM learning with the PjBL model. Creativity data was taken with a creativity test instrument with a reliability of 0.84. Data analysis was carried out using ANCOVA followed by the effect size test. The results show that there are differences in students' creativity and understanding of concepts were taught by STEM learning with PjBL and conventional models. The effectiveness of STEM learning with the PjBL model on creativity and understanding of science concepts for elementary school students is significant in large categoriesAbstrak: Penelitian ini bertujuan untuk mengkaji efektivitas pembelajaran STEM dengan model PjBL terhadap kreativitas dan pemahaman konsep siswa sekolah dasar. Rancangan yang digunakan dalam penelitian ini adalah quasy experimental design. Subjek penlitian 60 siswa sekolah dasar yang terbagi dalam 2 kelas  homogen yaitu 30 siswa di kelas eksperimen dan 30 siswa di kelas eksperimen.Siswa di kelas kontrol dilakukan pembelajaran konvensional dan di kelas eksperimen dilakukan pembelajaran STEM dengan model PjBL.Data kreativitas diambil dengan instrument tes kreativitas dengan reliabilitas 0,84. Anlisis data dilakukan menggunakan ANCOVA dilanjutkan uji effect size. Hasil penelitian menujukkan bahwa ada perbedaan kreativitas dan pemahaman konsep siswa yang dilakukan pembelajarn STEM dengan model PjBL dan konvensional. Efektivitas pembelajaran STEM dengan model PjBL terhadap kreativitas dan pemhaman konsep IPA  siswa sekolah dasar signifikan dengan kategori besar.